Therapeutic Efficacy and Safety of Fractional Carbon dioxide Laser versus Q-Switched Nd:YAG 1064 nm Laser in the treatment of Melasma- A Comparative Interventional Study - Kiran Irfan Ali; Ghias, Aisha; Wajieha Saeed; Zaima Sohail Chaudhry; Kainat Zaffar Laghari; Zaib; Shahbaz Aman (Journal of Pakistan Association of Dermatologists, 2023)
Objective To compare the efficacy and safety profile of fractional CO2 laser versus Q-switched Nd:YAG 1,064 nm laser while treating various subtypes of melasma. Â Methods Eighty six patients of 18 years to 40 years of either gender, suffering from Melasma involving superficial epidermis, deep dermal melanosis or with coexisting both subtypes not taking any treatment for last 6 months were included. Patients with cutaneous and systemic co-morbidities were excluded. Pre-treatment MASI was calculated. Patients were randomized into two Groups, Group A and Group B with 43 patients each, with resistant melasma underwent Fractional Carbondioxide Laser and Q-Switched Nd:YAG 1064 nm Laser respectively. Treatment was done every four weeks for five consecutive sessions and response was assessed at one month follow up. Pictorial evidence of facial cutaneous melanosis was made into account using a DSLR camera at their first presentation to keep a record of primary lesion and prior to undergoing procedure (at four weeks interval) for comparison. Â Results Patients undergoing both the laser treatments mean age of 30.2Â±8.1 years. Fitzpatrick skin type V was most frequent followed by type IV. Majority (50.0%) had centrofacial melasma followed by malar (37.2%), mixed (9.3%) and mandibular (3.5%). It was epidermal in 52 (60.5%) patients while dermal and mixed in 14 (16.3%) and 20 (23.3%) patients respectively. A comparison between groups (A and B) was made on the basis of mean MASI score at presentation (16.4Â±12.9 vs. 16.8Â±18.6; p-value=0.921). Mean MASI score reduced significantly in both groups after 1 month of treatment; Group A (16.4Â±12.9 to 6.4Â±8.9; p-value<0.001) and Group B (16.8Â±18.6 to 12.3Â±15.2; p-value<0.001). The follow-up mean MASI score was markedly low in patients undergoing fractional CO2 laser in comparison with Q-switched Nd:YAG 1064 nm laser (6.4Â±8.9 vs. 12.3Â±15.2; p-value=0.030). Taking â‰¥60% reduction in baseline MASI score as efficacy, efficacy was significantly higher in cases with fractional CO2 laser treatment than Q-Switched Nd:YAG 1064 nm laser (86.0% vs.46.5%; p-value<0.001). Â Conclusion Â Fractional CO2 laser is more efficacious in treating melasma. Â